2022
DOI: 10.7554/elife.70586
|View full text |Cite
|
Sign up to set email alerts
|

A dentate gyrus-CA3 inhibitory circuit promotes evolution of hippocampal-cortical ensembles during memory consolidation

Abstract: Memories encoded in the dentate gyrus (DG) - CA3 circuit of the hippocampus are routed from CA1 to anterior cingulate cortex (ACC) for consolidation. Although CA1 parvalbumin inhibitory neurons (PV INs) orchestrate hippocampal-cortical communication, we know less about CA3 PV INs or DG - CA3 principal neuron - IN circuit mechanisms that contribute to evolution of hippocampal-cortical ensembles during memory consolidation. Using viral genetics to selectively mimic and boost an endogenous learning-dependent circ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 85 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…PV mediated perisomatic inhibitory synaptic transmission in downstream principal neurons (CA3/CA2) may facilitate encoding, routing and consolidation of experiential information in distinct neuronal ensembles by imposing a sparse activity regimen (Mori et al, 2007;Neubrandt et al, 2017;Pelkey et al, 2017;Torborg et al, 2010), synchronizing activity of principal cells and generation of network oscillations (Amilhon et al, 2015;Buzsaki, 2015;Cardin et al, 2009;Csicsvari et al, 2000;de la Prida et al, 2006;Gan et al, 2016;Hu et al, 2014;Klausberger et al, 2003;Ognjanovski et al, 2017;Sohal et al, 2009). Consistently, we recently demonstrated that increasing feed-forward inhibition (FFI) in DG-CA3 resulted in enhanced stability and precision of context-associated neuronal ensembles and hippocampal-cortical synchrony (Twarkowski et al, 2022). Whether DGC recruitment of PV IN mediated inhibition of CA3 and CA2 is necessary for encoding social experiences is not known.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…PV mediated perisomatic inhibitory synaptic transmission in downstream principal neurons (CA3/CA2) may facilitate encoding, routing and consolidation of experiential information in distinct neuronal ensembles by imposing a sparse activity regimen (Mori et al, 2007;Neubrandt et al, 2017;Pelkey et al, 2017;Torborg et al, 2010), synchronizing activity of principal cells and generation of network oscillations (Amilhon et al, 2015;Buzsaki, 2015;Cardin et al, 2009;Csicsvari et al, 2000;de la Prida et al, 2006;Gan et al, 2016;Hu et al, 2014;Klausberger et al, 2003;Ognjanovski et al, 2017;Sohal et al, 2009). Consistently, we recently demonstrated that increasing feed-forward inhibition (FFI) in DG-CA3 resulted in enhanced stability and precision of context-associated neuronal ensembles and hippocampal-cortical synchrony (Twarkowski et al, 2022). Whether DGC recruitment of PV IN mediated inhibition of CA3 and CA2 is necessary for encoding social experiences is not known.…”
Section: Introductionmentioning
confidence: 59%
“…Learning increases mossy fiber excitatory drive onto PV INs (Caroni, 2015; Guo et al, 2018; Ruediger et al, 2012; Ruediger et al, 2011; Twarkowski et al, 2022) and enhances PV IN perisomatic contacts (“PV IN plasticity”) in CA3 (Guo et al, 2018; Twarkowski et al, 2022). To determine if social experience also increases FFI connectivity and PV IN plasticity in CA3/CA2, lentiviruses expressing GFP (CaMKIIα-GFP) were injected into the DG of 2-months old Dyrk1a +/+ mice two weeks prior to habituation to a context over 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can lead to inappropriate anxiety (4) and disturb the ability to discriminate threats from safety (5). Strikingly, remote memories are more generalized than recent ones, which suggests a time-dependent reorganization in hippocampal-cortical networks (6)(7)(8)(9)(10). Therefore, a better understanding of such remote memory generalization mechanisms may thus guide the search for an effective new intervention strategies.…”
Section: Introductionmentioning
confidence: 99%